Malay Stilt House Literacy for Strengthening Environmental Education - Nadia Putri Amanda Nasution; Sakti Ritonga (MASI Mandiri Edukasi, 2025)
This study examines the local wisdom values embedded in the architecture of Malay stilt houses as a literacy medium for environmental education. Malay stilt houses reflect cultural identity and embody sustainability principles relevant to current environmental challenges. The research employed a qualitative descriptive method, utilising in-depth interviews, field observations, and documentation. The study was conducted in AUR Village, Medan Maimun District, Medan City, with informants of traditional leaders, local educators, and residents of stilt houses who directly know these structures' cultural and environmental significance. The findings indicate that Malay stilt houses promote values such as adaptation to natural conditions, energy efficiency, vegetation preservation, and environmentally friendly building materials. These houses hold strong potential as a medium for environmental literacy, as they integrate cultural heritage, ecological awareness, and sustainable living practices. By incorporating the study of Malay stilt houses into educational activities, the younger generation can develop a sense of pride in local culture and a deeper understanding of and responsibility for environmental conservation.